2010
DOI: 10.1016/j.biocontrol.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) on potted greenhouse chrysanthemum

Abstract: a b s t r a c tDispersal of natural enemies through a crop is a key component of biological control. The release strategy should optimize the number of predators that are released, the release frequency and number of release sites throughout a crop with regards to the distance that natural enemies can disperse from their release point. In this study, dispersal rate and behaviour of Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) was investigated in potted greenhouse chrysanthemums in the presence or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 16 publications
5
22
0
2
Order By: Relevance
“…The layout of the crop is therefore one of the most important factors to consider when choosing an A. swirskii introduction method in a greenhouse. Buitenhuis et al (2010a) demonstrated that A. swirskii effectively stay on the potted ornamental plant on which they are released; approximately a quarter of the mites walked down the pot to the ground, but only a few individuals were recovered from adjacent pots. Only when plant canopies of adjacent pots were touching, A. swirskii freely moved between plants.…”
Section: Production Practicesmentioning
confidence: 98%
“…The layout of the crop is therefore one of the most important factors to consider when choosing an A. swirskii introduction method in a greenhouse. Buitenhuis et al (2010a) demonstrated that A. swirskii effectively stay on the potted ornamental plant on which they are released; approximately a quarter of the mites walked down the pot to the ground, but only a few individuals were recovered from adjacent pots. Only when plant canopies of adjacent pots were touching, A. swirskii freely moved between plants.…”
Section: Production Practicesmentioning
confidence: 98%
“…Although not much is known about the dispersal of natural enemies throughout a crop, it is a key component of successful biological control (Buitenhuis et al 2010). Some studies have focused on the attraction of Orius spp.…”
Section: Introductionmentioning
confidence: 99%
“…They cause direct damage when they extract plant fluids and indirect damage by transmitting viral pathogens (Byrne and Bellows 1991;Foster et al 2007). In this work, we have focused on three pest species of high agricultural importance: Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), Myzus persicae (Sulzer) (Hemiptera: Aphididae) and Macrosiphum euphorbiae (Thomas) (Hemiptera: Aphididae) and on two predators commonly released in protected crops for controlling B.tabaci and other key-pests: Orius laevigatus (Fieber) (Hemiptera: Anthocoridae) and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) (Bosco et al 2008;Buitenhuis et al 2010;Colomer et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As this mite originates from the Mediterranean basin, mostly found in humid coastal areas, A. swirskii prefer high temperatures and have a critical RH limit of ~70%, anything lower may cause their eggs to desiccate (de Moraes et al, 2004;Ferrero et al, 2010;Porath & Swirski, 1965). Buitenhuis et al (2010a) recently discovered that A. swirskii does not disperse well when applied to separated plants. Only a small percentage of the population applied to the upper foliage of the plant moved down to the soil in order to disperse through the greenhouse to neighbouring plants.…”
Section: Acari (Mites)mentioning
confidence: 99%
“…Only a small percentage of the population applied to the upper foliage of the plant moved down to the soil in order to disperse through the greenhouse to neighbouring plants. Buitenhuis et al (2010a) (Buitenhuis et al, 2010a). …”
Section: Acari (Mites)mentioning
confidence: 99%